2006
DOI: 10.1088/0305-4470/39/10/001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of economic interactions on credit risk

Abstract: Abstract. We study a credit risk model which captures effects of economic interactions on a firm's default probability. Economic interactions are represented as a functionally defined graph, and the existence of both cooperative, and competitive, business relations is taken into account. We provide an analytic solution of the model in a limit where the number of business relations of each company is large, but the overall fraction of the economy with which a given company interacts may be small. While the effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 34 publications
3
44
0
Order By: Relevance
“…2 and 3. We note that the tails of the loss-frequency distribution and the loss distribution are more pronounced than in our previous study [11]. This solely due to the fact that in the present paper we followed the Basel II suggestion that relates the coupling of a company to macro-economic factors with its default probability via (4).…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…2 and 3. We note that the tails of the loss-frequency distribution and the loss distribution are more pronounced than in our previous study [11]. This solely due to the fact that in the present paper we followed the Basel II suggestion that relates the coupling of a company to macro-economic factors with its default probability via (4).…”
Section: Resultsmentioning
confidence: 58%
“…We have not looked specifically at finite size effects here. In [11] it was shown that they are fairly small. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In SVMs the volatility is changing randomly according to some stochastic differential equation or some discrete random processes. Recently, models of financial markets reproducing the most prominent statistical properties of stock market data, whose dynamics is governed by non-linear stochastic differential equations, have been proposed [Malcai et al, 2002;Borland, 2002;Borland, 2002b;Hatchett & Kühn, 2006;Bouchaud & Cont, 1998;Bouchaud, 2001;Bouchaud, 2002;Sornette, 2003;Bonanno et al, 2006;Bonanno et al, 2007].…”
Section: Introductionmentioning
confidence: 99%